Modelling the effects of sediment on the seismic behaviour of Kinta roller compacted concrete dam - Abdul Malik Thanoon, Huda; Jaafar, Mohd Saleh; Noorzaei, Jamaloddin; Abdul Malik Thanoon, Waleed; Mohammed, Thamer Ahmed (Universiti Putra Malaysia Press, 2010)
An attempt was made in this investigation to trace the dynamic response of roller compacted concrete dam, which is subjected to horizontal ground motion by considering the interactions between flexible foundations, reservoir water, and bottom reservoir sediments. Two-dimensional finite-infinite element was used for the non-linear elasto-plastic dynamic analysis. In this analysis, special emphasis was given to the non-linear behaviour of discontinuities along RCC dam-bedding rock foundation which was modelled by thin layer interface. Analysis was first carried out under static loading (self-weight and hydrostatic pressure), and this this was followed by seismic analysis, with hydrodynamic pressure effect in a dam-reservoir system. Based on the numerical dynamic results, it is concluded that the bottom reservoir sediment has significant effect on the seismic response of the RCC gravity dam. Moreover, there is a redistribution of the stresses at thin layer interface with significant stresses reduction, which is resulted from the release of energy through different modes of deformation in this region.